2020
DOI: 10.2147/cmar.s246272
|View full text |Cite
|
Sign up to set email alerts
|

<p>Circular RNA circNRIP1 Sponges microRNA-138-5p to Maintain Hypoxia-Induced Resistance to 5-Fluorouracil Through HIF-1α-Dependent Glucose Metabolism in Gastric Carcinoma</p>

Abstract: Background: Hypoxia-induced chemoresistance is recognized as a major obstacle to the successful treatment of gastric cancer (GC). Circular RNAs (circRNAs) have been proposed to implicate in resistance to chemotherapeutic drugs. However, whether circNRIP1 is involved in the development of hypoxia-induced 5-fluorouracil (5-FU) resistance remains largely unknown. Methods: Gene expression was evaluated using quantitative real-time polymerase chain reaction and Western blot. The impact of circNRIP1 on hypoxia-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 40 publications
0
35
1
Order By: Relevance
“… 14 In addition, Xu et al demonstrated that circ_0004771 could regulate hypoxia-mediated 5-Fluorouracil resistance to gastric cancer. 15 Huang et al also illustrated that circ_0001946 repressed lung cancer development and regulated DDP resistance. 16 However, the effects of circASXL1 on DDP resistance and NSCLC progression under hypoxia were unknown.…”
Section: Introductionmentioning
confidence: 98%
“… 14 In addition, Xu et al demonstrated that circ_0004771 could regulate hypoxia-mediated 5-Fluorouracil resistance to gastric cancer. 15 Huang et al also illustrated that circ_0001946 repressed lung cancer development and regulated DDP resistance. 16 However, the effects of circASXL1 on DDP resistance and NSCLC progression under hypoxia were unknown.…”
Section: Introductionmentioning
confidence: 98%
“… 29 Additionally, miR-138-5p was sponged by circular RNA circNRIP1, involved in hypoxia-induced 5-FU resistance of GC cells. 30 Similarly, downregulation of miR-138-5p was detected in GC tissues and cells. Apart from this, interference of miR-138-5p largely weakened the inhibition effect of circ_CORO1C knockdown on GC development, indicating that circ_CORO1C exerted its oncogenic role by absorbing miR-138-5p.…”
Section: Discussionmentioning
confidence: 92%
“…According to research, the biological function of circRNAs is separated into the following categories: act as a miRNA sponge, 17 a RNA‐binding proteins and protein decoys, 18 a regulators of transcription 19,20 . Interestingly, miRNA sponging, which is circRNA act as competitive endogenous RNA (ceRNA) to keep miRNA away from their target gene, is the most commonly reported role of circRNAs 21 . For example, circular RNA circCCDC9 can act as a miR‐6792‐3p sponge to suppress the progression of gastric cancer through regulating CAV1 expression 22 .…”
Section: Introductionmentioning
confidence: 99%